2018
DOI: 10.1130/ges01588.1
|View full text |Cite
|
Sign up to set email alerts
|

The Mystic subterrane (partly) demystified: New data from the Farewell terrane and adjacent rocks, interior Alaska

Abstract: The youngest part of the Farewell terrane in interior Alaska (USA) is the enigmatic Devonian-Cretaceous Mystic subterrane. New U-Pb detrital zircon, fossil, geochemical, neodymium isotopic, and petrographic data illuminate the origin of the rocks of this subterrane. The Devonian-Permian Sheep Creek Formation yielded youngest detrital zircons of Devonian age, major detrital zircon age probability peaks between ca. 460 and 405 Ma, and overall age spectra like those from the underlying Dillinger subterrane. Sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 79 publications
1
31
0
Order By: Relevance
“…The detrital U/Pb ages from modern rivers match bedrock igneous ages and suggest that the vast majority of zircon and apatite in modern rivers are derived from this plutonic belt. We directly compare our modern river ages with bedrock ages for a portion of the western Alaska Range (Figure a) where a large number of ZUPb ages have been determined from igneous bedrock [ Jones et al , ] and detrital bedrock [ Box et al , ; Karl et al , ; Dumoulin et al , ]. Igneous bedrock ages are distinct from detrital bedrock ages in all cases except for 90–110 Ma ages, which are present in both.…”
Section: Resultsmentioning
confidence: 99%
“…The detrital U/Pb ages from modern rivers match bedrock igneous ages and suggest that the vast majority of zircon and apatite in modern rivers are derived from this plutonic belt. We directly compare our modern river ages with bedrock ages for a portion of the western Alaska Range (Figure a) where a large number of ZUPb ages have been determined from igneous bedrock [ Jones et al , ] and detrital bedrock [ Box et al , ; Karl et al , ; Dumoulin et al , ]. Igneous bedrock ages are distinct from detrital bedrock ages in all cases except for 90–110 Ma ages, which are present in both.…”
Section: Resultsmentioning
confidence: 99%
“…The northwestern area of the cross section (Figs. 2 and 3) exposes deformed strata of the Dillinger and Mystic subterranes of the Farewell terrane (Dumoulin et al, 2018a(Dumoulin et al, , 2018b. These thin-bedded carbonates and siliciclastic turbidite strata are cut by top-to-the-northwest thrust faults and have been deformed into northwest-vergent overturned folds (Bundtzen et al, 1997; see subsequent section on "Deformation of the Kahiltna assemblage").…”
Section: Older Strata Northwest Of the Kahiltna Assemblagementioning
confidence: 98%
“…macrofossil occurrences (Csejtey et al, 1992;Bundtzen et al, 1997;Reed and Nelson, 1980). However, Dumoulin et al (2018b) suggested that some, and perhaps all, of the Valanginian and Hauterivian-Barremian fossil localities along or near the northwestern margin of the northwestern succession are part of the underlying Mystic subterrane of the Farewell terrane, and not the Kahiltna assemblage.…”
Section: ■ Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, shallow-water carbonate rocks and limestone turbidites make up most of the Devonian section in the Farewell terrane, along with subordinate heterolithic sandstones. Upper Devonian strata in the Mystic subterrane have features indicating a high-productivity setting, such as phosphatic nodules and sedimentary barite deposits (Reed and Nelson, 1980;Bundtzen and Gilbert, 1991;Dumoulin et al, 2014b); these distinctive deposits have no counterparts in the Alexander terrane or Arctic Alaska.…”
Section: Silurian-devonianmentioning
confidence: 99%